2021
DOI: 10.3390/jcm10091975
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Different Indexes of Adiposity and Body Composition for the Identification of Metabolic Syndrome in Women with Obesity

Abstract: The aim of this study was to compare the accuracy of different indexes of adiposity and/or body composition in identifying the metabolic syndrome (MetS) in a group of 1528 Caucasian women with obesity: (age ± standard deviation (SD): 50.8 ± 14 years (range 18–83); body mass index (BMI) 43.3 ± 5.9 kg/m2 (30.7–72.9 kg/m2)). The following indexes were assessed in each subject: BMI, fat-free mass index (FFMI), fat mass index (FMI), tri-ponderal mass index (TMI), waist-to-height ratio (WtHR), and the body mass fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 29 publications
3
12
2
Order By: Relevance
“…Obesity indexes were estimated in all T2DM patients, and data showed that BMI, WC, VAI, BF%, BRI, and LAP were higher in MetS+ patients compared with MetS-patients. These results were consistent with the result of Radetti et al 35 , who reported that MetS+ patients have the highest average of both WC and BMI compared with Met-patients. After that, Obesity indexes were evaluated in MetS+ patients and compared according to the number of metabolic syndrome components (MetS-3, MetS-4, and MetS-5), the average of BF%, VAI, and LAP increased with the increasing number of components, while BMI, WC, and BRI did not show a statistically significant difference.…”
Section: Discussionsupporting
confidence: 93%
“…Obesity indexes were estimated in all T2DM patients, and data showed that BMI, WC, VAI, BF%, BRI, and LAP were higher in MetS+ patients compared with MetS-patients. These results were consistent with the result of Radetti et al 35 , who reported that MetS+ patients have the highest average of both WC and BMI compared with Met-patients. After that, Obesity indexes were evaluated in MetS+ patients and compared according to the number of metabolic syndrome components (MetS-3, MetS-4, and MetS-5), the average of BF%, VAI, and LAP increased with the increasing number of components, while BMI, WC, and BRI did not show a statistically significant difference.…”
Section: Discussionsupporting
confidence: 93%
“…Several authors have demonstrated the interest in estimating the body composition and fat distribution in adults using anthropometric measures [ 46 , 47 , 48 , 49 ], however few studies explored the relation between TBW and obesity. In the current study, TBW (a) correlated with the following anthropometric measures NC, C-index, MAC, WC, HC, BMI, BM and WHR ( Table 2 and Figure 3 ) and (b) with Multiple linear regression analysis, presented positive coefficients to NC, ABSI, WHR and BM, and negative coefficient to C-index ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The objective is to find the simplest and least expensive tool that can identify the probability of having MetS in obese subjects, avoiding unnecessary investigation. In this context, we have previously compared indexes requiring or not instrumental support in a large group of children and adolescents, with different degrees of obesity [ 19 ]. We demonstrated that the indexes that considered body composition, as assessed by Bioelectrical Impedance Analysis (BIA), did not perform better than BMI for detecting MetS.…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that the indexes that considered body composition, as assessed by Bioelectrical Impedance Analysis (BIA), did not perform better than BMI for detecting MetS. More recently, we have demonstrated that the evaluation of body composition throughout BIA did not add any additional value to simple anthropometric measures, such as BMI or WtHR, in identifying the risk of MetS in a large number of obese women [ 19 ].…”
Section: Introductionmentioning
confidence: 99%